Pengaruh Media Edukasi Ular Tangga Terhadap Pengetahuan Menstrual Hygiene Pada Remaja Intellectual Disability di SLB Kabupaten Bantul - Dwi Yati; Andriyani, Fifi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Teenagers who have reached puberty will start having periods. Adolescents with intellectual disabilities will also experience this condition like typical adolescents. Therefore, it is crucial to teach adolescents about menstrual hygiene through health education using snake and ladder media to prevent infection of the reproductive organs. Objective: To determine how snake and ladder educational media affect adolescents with intellectual disabilities in the SLB Kabupaten Bantul knowledge of menstrual hygiene. Methods: This study employed a pre-experimental design with One Group Pre Test- Post Test. A total of 30 respondents were sampled using a total sampling technique. Data was collected in June 2022 at SLB PGRI Trimulyo Bantul and SLB Ma'arif Bantul. A questionnaire on the level of knowledge of menstrual hygiene for adolescents with intellectual disabilities and educational media for snakes and ladders were used as research instruments. The Wilcoxon Signed Ranks Test was used to analyze the study's findings. Results: The findings revealed that prior to receiving an education using snakes and ladders, participants had good knowledge (6.7%), sufficient knowledge (33.3%), and insufficient knowledge (60%). Following education with snakes and ladders, knowledge increased to good (46.7%), sufficient (50.0%), and insufficient (1.9%). The data was strengthened by the Wilcoxon Signed Ranks Test results, which yielded a value of p = 0.001. Conclusion: Educational media on snakes and ladders affects knowledge of menstrual hygiene in adolescents with intellectual disabilities in SLB Kabupaten Bantul. It is hoped that adolescents can continue to increase their knowledge regarding menstrual hygiene by seeking information sources from schools and health workers.